Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Ge, Meiling; Mo, Jing; Ip, Jack Chi-Ho; Li, Yixuan; Shi, Wenge; Wang, Zongling; Zhang, Xuelei; Xu, Qinzeng (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers (18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.